1994
DOI: 10.1111/j.1365-2729.1994.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The changing picture of IT experience in post‐graduate teacher training

Abstract: The level and kind of Information Technology (IT) experience which our Postgraduate Certificate of Education (PGCE) students bring with them when they start their training is changing rapidly. This paper compares the IT experience and perceived training needs of two cohorts of primary and secondary PGCE students two years apart, 1989/90 and 1991/92. Many of the findings of the first survey were replicated in the second: there was comparatively little use of computers outside word processing and databases, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, the recent work of Mellar and Jackson (1994) suggests that this approach is problematic, demonstrating that the student-teacher population, for any one university, is likely to encompass wide variations in IT-related attitudes, expectations and experience; and that '. .…”
Section: A Failure Of Purposementioning
confidence: 99%
“…However, the recent work of Mellar and Jackson (1994) suggests that this approach is problematic, demonstrating that the student-teacher population, for any one university, is likely to encompass wide variations in IT-related attitudes, expectations and experience; and that '. .…”
Section: A Failure Of Purposementioning
confidence: 99%
“…Many of the mature students have worked in science-related posts that require high levels of IT expertise. Mellar & Jackson (1994) have made similar comments based on their longitudinal study of the IT competence of student teachers from a wide range of disciplines. Why is it then that we appear to be failing to build on this expertise and that science is still in the backwater when it comes to using IT in school?…”
Section: Discussionmentioning
confidence: 83%
“…The picture appears equally dismal when questions concerning teachers' competence are raised -recently qualified teachers seem no better prepared for the use of IT in the teaching of mathematics than teachers trained earlier. This reflects concerns raised by Mellar & Jackson (1994) who found that: "the range of applications that students have met remains very worrying . .…”
Section: Teachers Whose First Computer Experiences Were Gained In Indmentioning
confidence: 87%
“…Several possible ways forward are proposed. One path might be for trainers to ask trainees to identify their needs and gear their courses to the responses (Mellar & Jackson, 1994) although this would necessitate acknowledgment that a beginner may not be aware of his or her particular needs. A needs identification process would also preserve the rights of those with no interest in computers to continue as they are whilst facilitating the development of those who wish to embrace change (Veen, 1993).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation